Early and Intensive Dietary Counseling in Lung Cancer Patients Receiving (Chemo)Radiotherapy—A Pilot Randomized Controlled Trial. (17th August 2016) - Kiss, Nicole; Isenring, Elisabeth; Gough, Karla; Wheeler, Greg; Wirth, Andrew; Campbell, Belinda A.; Krishnasamy, Meinir
ABSTRACT: Malnutrition is prevalent in patients undergoing (chemo)radiotherapy (RT) for lung cancer. This pilot study tested the feasibility and acceptability of delivering an intensive nutrition intervention for lung cancer patients receiving RT. Twenty-four patients with lung cancer were randomized to receive the intervention which employed a care pathway to guide intensive dietary counseling from pretreatment until 6-wk posttreatment or usual care. Nutritional, fatigue, and functional outcomes were assessed using valid and reliable questionnaires before randomization, at the start and end of RT and 1- and 3-mo post-RT. Consent rate was 57% with an overall attrition of 37%. Subject compliance with the completion of study questionnaires was 100%. A clinically important mean difference indicated greater overall satisfaction with nutritional care in the intervention group (5.00, interquartile range [IQR] 4.50–5.00; 4.00, IQR 4.00–4.00). Clinically important differences favoring the intervention were observed for weight (3.0 kg; 95% confidence interval [CI] −0.8, 6.8), fat-free mass (0.6 kg; 95% CI −2.1, 3.3), physical well-being (2.1; 95% CI −2.3, 6.5), and functional well-being (5.1; 95% CI 1.6, 8.6), but all 95% CIs were wide and most included zero. Recruitment feasibility and acceptability of the intervention were demonstrated, which suggest larger trials using an intensive nutrition intervention would be achievable.